2023
DOI: 10.9734/ajaees/2023/v41i11827
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Food Insecurity among Rural Farming Households: Evidence from Ikere Local Government Area of Ekiti State, Nigeria

Abstract: Food insecurity is a major global challenge that is more prevalent in developing nations like Nigeria with varying degrees of impact on households and demanding immediate attention from policymakers. This study assessed the level of insecurity among farming households in Ikere Local Government Area of Ekiti State, Nigeria using the Household Food Insecurity Access Scale (HFIAS) approach. The data for the study was collected from 140 farming households selected using a two-stage sampling technique. Descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Otekunrin et al (2021) found that among Nigerian agricultural families, food insecurity is more common when non-farm income is high. Ajao et al (2023) also found that food insecurity is best measured by how easy it is to get enough food, therefore our results are in line with theirs (Mundowa & Mumbengegwi, 2020).…”
Section: Empirical Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…Otekunrin et al (2021) found that among Nigerian agricultural families, food insecurity is more common when non-farm income is high. Ajao et al (2023) also found that food insecurity is best measured by how easy it is to get enough food, therefore our results are in line with theirs (Mundowa & Mumbengegwi, 2020).…”
Section: Empirical Reviewsupporting
confidence: 91%
“…Furthermore, the research found that families led by women are more likely to experience food insecurity due to factors such as marital status and educational level. Nkomoki et al (2019) found that households with more cattle had a lower likelihood of food insecurity, and our results are in line with that (Ajao et al, 2023). Otekunrin et al (2021) found that among Nigerian agricultural families, food insecurity is more common when non-farm income is high.…”
Section: Empirical Reviewsupporting
confidence: 91%
“…Analysis of data to ascertain the level of food insecurity among 451 households in rural northern Nigeria showed that more than 50% of the households are food insecure (Oyedira and Olajid, 2023). Evidence of food insecurity among farming households in Ikere Local Government Area of Ekiti State, Nigeria, using the Household Food Insecurity Access Scale (HFIAS) approach, showed that 83.7% of the households were food insecure at varying levels (Ajao et al 2023). The prevalence of food insecurity among 3519 pregnant women aged 15-49 years studied by Ujah et al (2023) found that nearly 75% 58 reporting moderate to severe food insecurity.…”
Section: A Brief Overview Of Recent Studies On Hunger Food Insecurity...mentioning
confidence: 99%